(untitled) (Advancements in Homeopathic Research, 2022)
Background and aim : Simple (childhood) myopia is a common variety of myopia that progress during the period of body growth and stabilize by early twenties. Heredity plays an important role in its incidence however increased prevalence and its progression during last few decades especially in Asian countries was mainly attributed to excessive near work. Out of different studies done so far to control myopia, topical use of modern medicine Atropine 1% was found effective in controlling myopia but has side effect, ethical issues and rebound effect after cessation of treatment. Homoeopathy mentions medicines for myopia, out of which Ruta graveolens (Ruta) seems to have more similarity to myopia associated with excessive near work due to its action on accommodation and sclera. In homoeopathy hereditary diseases are treated by use of individualized medicines that helps to correct abnormal susceptibility in an individual. So these medicines were used in this study with an aim to evaluate the effect of Ruta 3C followed by individualized homoeopathic (IH) treatment on annual myopia progression rate in patients suffering from simple myopia. Material and Methods: Eleven cases of simple myopia in progressive stage were studied retrospectively from the record of institute’s OPD. Subjects aged 8 to 16 years and myopia of -1.5 to -7.0 diopters (D) were included. Myopia or spherical equivalent of refraction (SER) before starting the treatment was assessed from previous refraction reports. Ruta 3C in BD dose was used orally for 2 years with a gap of 7 days after every 21 days of medication. Thereafter Individualized homoeopathic (IH) treatment was given and subjective refraction